Less restrictive birth control, less education? Evidence from ethnic minorities in China - Yishen Liu; Yao Pan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper investigates the net impact of birth control policy in China on educational attainment of the partially excluded ethnic minorities. Exploring county-level variation in the value of fines levied for unsanctioned births, we show that more stringent enforcement of the birth control policy reduces educational attainment of urban ethnic minorities. Suggestive evidence shows this negative impact is likely to reflect the spillover effect from improved quality of ethnic majority children. For rural ethnic minorities, however, the level of enforcement of the birth control policy does not significantly affect education. The documented negative impact on education of urban ethnic minorities, combined with the improved quality found for both rural and urban ethnic majorities, implies that the birth control policy substantially contributes to the rising educational gap between ethnic minorities and majorities in China.
Keywords: I21; I24; J15; J13; 330; birth control; education; minority; quantity-quality tradeoff; China